Organizational Impression Management StrategiesAnd Its Relationship to the Employment Voice Behaviors:Case Study to the AL-Rasheed Bank Branches in AL-Najaf Province - AL- Hadrawi, Rafid (The Arab Journal of Administration, 2019)
Purpose: This paper was an attempt realistic problem embodies a number of intellectual and practical questions, answers targeted to identify the intellectual frameworks for the variables of paper) i.e. organizational impression management strategies and Employment voice behaviors (. These variables are important topics and modern in relation to the Iraqi environment in general and the banking sector in particular. As well as to identify the level of practice of the research sample) represented by AL- Kufa, AL- Roada, AL- Sadiq St. and AL- Manadhra Branchs of Al Rasheed bank in Najaf( for organizational impression management strategies and Employment voice behaviors, and verify their influence on this sector. Methodology / Design: that studies in the paper adopts a case study methodology to the branches of AL-Rasheed Bank in AL-Najaf province in order to accurately obtain the required data and information. Basically, two major procedures are employed in the data collecting process, which is conducting personal interviews with several individuals the sample, as well as the use a questionnaire form. In this regard, a selected sample of the employees has been presented the questionnaire form. The employees sample include: manager, associate manager, observant head, accountant, observant, cashiers (who work at the bank branches and are asked to respond to the) 7 (items of the questionnaire. These items are distributed over the research variables and their subsidiary dimensions. Moreover, the number of responded who fully answered the questionnaires items is )117(employees that form 77% of the entire research Population that amount to )1 2(employees. Also, a statistical means represented by) SPSS20( Software is used to analyze and process the collected data and Information Research value: The current paper has arrived at number theoretical and applicative) practical (conclusions that actualize and reveal the status of organizational impression management strategies. The most the most important conclusions are: First intimidation strategy has a counteractive impact employing employee voice behaviors, i.e. Employees show objection to the use of this strategy by their leaders. Therefore, it is recommended here to avoid or stop using the practice of this strategy, since it gives a negative impression to the employees in relation to the bank at which thy work.